An Enduring Somatic Threat Model of Posttraumatic Stress Disorder Due to Acute Life-Threatening Medical Events - Edmondson, Donald (2014)
Posttraumatic stress disorder (PTSD) occurs in 12-25% of survivors of acute life-threatening medical events such as heart attack, stroke, and cancer, and is associated with recurrence of cardiac events and mortality in heart attack survivors. This article reviews the current state of knowledge about PTSD after such events, and proposes an Enduring Somatic Threat (EST) model of PTSD due to acute life-threatening medical events to address underappreciated differences between PTSD due to past, discrete/external traumatic events (such as combat) and PTSD due to acute manifestations of chronic disease that are enduring/internal in nature (such as heart attack and stroke). The differences include the external versus internal/somatic source of the threat, the past versus present/future temporal focus of threatening cognitions, the different types and consequences of avoidance behavior, and the different character and consequences of hyperarousal. Although important differences between the two types of PTSD exist, the EST model proposes that the underlying fear of mortality maintains PTSD symptoms due to both discrete/external and ongoing/somatic events. Finally, this article offers a research agenda for testing the EST model, with a particular focus on areas that may improve cardiovascular prognosis and health behaviors in survivors of heart attack and stroke.